Food guide of the Mexicanized Mediterranean Diet - Sierra, Ángel; Cortés-García, María Fernanda; Hernández-Nuñez, Yulisa; Priego-Álvarez, Heberto Romeo; Vergara-Galicia, Jorge; Hernández-Díaz, Vanesa (Horizonte Sanitario, 2022)
Objective: To create the infographic of the Mexicanized Mediterranean Diet food guide and evaluate its understanding. Material and Methods: Descriptive type study, which consisted of two phases, the 1st. The infographic of the Mexicanized Mediterranean Diet food guide was created. 2nd Appreciation and comprehension of the food guide infographic was evaluated online for the university population, including relatives and acquaintances. Results: 273 participants with an average age of 42, 74% women and 26% men, more than 94% of the participants responded that they understood the infographic in its entirety. DMM is practical, applicable, affordable, understandable, good for humans and the environment. Conclusion: The Mediterranean Diet can partially or totally prevent metabolic syndrome, the Mexicanized Mediterranean Diet food guide promotes a healthy life and well-being for all ages, supports the objectives of sustainable development, will be a practical, applicable public health tool, affordable, understandable, suitable for promotion in the Mexican population. Keywords: Mediterranean Diet; Prevention; Dietary guidelines; Metabolic syndrome